Keterampilan Menulis Karangan Narasi Siswa Kelas 5 Sekolah Dasar - Dina Apri Salpianti; Febrina Dafit (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to determine the narrative essay writing skills of class 5D students at SD Negeri 17 Pekanbaru. This research is a qualitative descriptive study. The subjects of this research were class V teachers, as well as all class 5D students at SD Negeri 17 Pekanbaru. The data collection techniques used were observation, interviews and documentation. The main instrument is the researcher using observation guide tools, interview guidelines, document review sheets. Data were analyzed through data reduction, data presentation, and drawing conclusions. The data validity checking technique uses triangulation of techniques and sources. The research results show that the narrative essay writing skills of class VD students at SD Negeri 17 Pekanbaru can still be said to be not optimal. This is because, there are still some students who are not correct in writing narrative essays as seen from the 5 criteria in this research, namely 1) Content, VD class students are not yet appropriate in developing content according to the theme and characters, plot and setting in students' narrative essays. clear. 2) Organizational Content, students are still wrong in determining the theme given by the teacher and the ideas written by students are not clear. 3) Grammar, students' use of grammar is still not correct. Students do not use subjects and predicates in writing narrative essays. 4) Word choice, students when writing narrative essays do not pay attention to writing capital letters and lower case letters. 5) Spelling and punctuation. The student's use of conjunctions is correct. However, students do not pay attention to the use of punctuation marks such as periods (.) and commas (,). This makes readers confused when reading students' narrative essays.